A Differential Equation is an equation with a function and one or more of its derivatives:
Example: an equation with the function y and its derivative dy dx
Here we will look at solving a special class of Differential Equations called First Order Linear Differential Equations
They are "First Order" when there is only dy dx , not d 2 y dx 2 or d 3 y dx 3 etc
A first order differential equation is linear when it can be made to look like this:
dy dx + P(x)y = Q(x)
Where P(x) and Q(x) are functions of x.
To solve it there is a special method:
And we also use the derivative of y=uv (see Derivative Rules (Product Rule) ):
dy dx = u dv dx + v du dx
Here is a step-by-step method for solving them:
Let's try an example to see:
Example 1: Solve this:dy dx − y x = 1
First, is this linear? Yes, as it is in the form
dy dx + P(x)y = Q(x)
where P(x) = − 1 x and Q(x) = 1
So let's follow the steps:
Step 1: Substitute y = uv, and dy dx = u dv dx + v du dx
So this: dy dx − y x = 1 Becomes this: u dv dx + v du dx − uv x = 1Step 2: Factor the parts involving v
Factor v: u dv dx + v( du dx − u x ) = 1Step 3: Put the v term equal to zero
v term equal to zero: du dx − u x = 0 So: du dx = u xStep 4: Solve using separation of variables to find u
Separate variables: du u = dx x Put integral sign: ∫ du u = ∫ dx x Integrate: ln(u) = ln(x) + C Make C = ln(k): ln(u) = ln(x) + ln(k) And so: u = kxStep 5: Substitute u back into the equation at Step 2
(Remember v term equals 0 so can be ignored): kx dv dx = 1Step 6: Solve this to find v
Separate variables: k dv = dx x Put integral sign: ∫ k dv = ∫ dx x Integrate: kv = ln(x) + C Make C = ln(c): kv = ln(x) + ln(c) And so: kv = ln(cx) And so: v = 1 k ln(cx)Step 7: Substitute into y = uv to find the solution to the original equation.
y = uv: y = kx 1 k ln(cx) Simplify: y = x ln(cx)And it produces this nice family of curves:
y = x ln(cx) for various values of c
What is the meaning of those curves?
They are the solution to the equation dy dx − y x = 1
Anywhere on any of those curves
the slope minus y x equals 1
Let's check a few points on the c=0.6 curve:
Estmating off the graph (to 1 decimal place):
Point | x | y | Slope ( dy dx ) | dy dx − y x |
---|---|---|---|---|
A | 0.6 | −0.6 | 0 | 0 − −0.6 0.6 = 0 + 1 = 1 |
B | 1.6 | 0 | 1 | 1 − 0 1.6 = 1 − 0 = 1 |
C | 2.5 | 1 | 1.4 | 1.4 − 1 2.5 = 1.4 − 0.4 = 1 |
Why not test a few points yourself? You can plot the curve here.
Perhaps another example to help you? Maybe a little harder?
Example 2: Solve this:dy dx − 3y x = x
First, is this linear? Yes, as it is in the form
dy dx + P(x)y = Q(x)
where P(x) = − 3 x and Q(x) = x
So let's follow the steps:
Step 1: Substitute y = uv, and dy dx = u dv dx + v du dx
So this: dy dx − 3y x = x Becomes this: u dv dx + v du dx − 3uv x = xStep 2: Factor the parts involving v
Factor v: u dv dx + v( du dx − 3u x ) = xStep 3: Put the v term equal to zero
v term = zero: du dx − 3u x = 0 So: du dx = 3u xStep 4: Solve using separation of variables to find u
Separate variables: du u = 3 dx x Put integral sign: ∫ du u = 3 ∫ dx x Integrate: ln(u) = 3 ln(x) + C Make C = −ln(k): ln(u) + ln(k) = 3ln(x) Then: uk = x 3 And so: u = x 3 kStep 5: Substitute u back into the equation at Step 2
(Remember v term equals 0 so can be ignored): ( x 3 k ) dv dx = xStep 6: Solve this to find v
Separate variables: dv = k x -2 dx Put integral sign: ∫ dv = ∫ k x -2 dx Integrate: v = −k x -1 + DStep 7: Substitute into y = uv to find the solution to the original equation.
y = uv: y = x 3 k ( −k x -1 + D ) Simplify: y = −x 2 + D k x 3 Replace D/k with a single constant c: y = c x 3 − x 2And it produces this nice family of curves:
y = c x 3 − x 2 for various values of c
And one more example, this time even harder:
Example 3: Solve this:dy dx + 2xy= −2x 3
First, is this linear? Yes, as it is in the form
dy dx + P(x)y = Q(x)
where P(x) = 2x and Q(x) = −2x 3
So let's follow the steps:
Step 1: Substitute y = uv, and dy dx = u dv dx + v du dx
So this: dy dx + 2xy= −2x 3 Becomes this: u dv dx + v du dx + 2xuv = −2x 3Step 2: Factor the parts involving v
Factor v: u dv dx + v( du dx + 2xu ) = −2x 3Step 3: Put the v term equal to zero
v term = zero: du dx + 2xu = 0Step 4: Solve using separation of variables to find u
Separate variables: du u = −2x dx Put integral sign: ∫ du u = −2 ∫ x dx Integrate: ln(u) = −x 2 + C Make C = −ln(k): ln(u) + ln(k) = −x 2 Then: uk = e -x 2 And so: u = e -x 2 kStep 5: Substitute u back into the equation at Step 2
(Remember v term equals 0 so can be ignored): ( e -x 2 k ) dv dx = −2x 3Step 6: Solve this to find v
Separate variables: dv = −2k x 3 e x 2 dx Put integral sign: ∫ dv = ∫ −2k x 3 e x 2 dx Integrate: v = oh no! this is hard!Let's see . we can integrate by parts. which says:
∫ RS dx = R ∫ S dx − ∫ R' ( ∫ S dx ) dx
(Side Note: we use R and S here, using u and v could be confusing as they already mean something else.)
Choosing R and S is very important, this is the best choice we found:
Put in R = −x 2 and S = 2x e x 2
And also R' = −2x and ∫ S dx = e x 2
So it becomes: v = −kx 2 ∫ 2x e x 2 dx − k ∫ −2x (e x 2 ) dx Now Integrate: v = −kx 2 e x 2 + k e x 2 + D Simplify: v = ke x 2 (1−x 2 ) + DStep 7: Substitute into y = uv to find the solution to the original equation.
y = uv: y = e -x 2 k ( ke x 2 (1−x 2 ) + D ) Simplify: y =1 − x 2 + ( D k )e - x 2 Replace D/k with a single constant c: y = 1 − x 2 + c e - x 2And we get this nice family of curves:
y = 1 − x 2 + c e - x 2 for various values of c